2020
DOI: 10.1111/acem.14062
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Topical Capsaicin Cream for Treatment of Cannabinoid Hyperemesis Syndrome

Abstract: Objectives: Patients with cannabinoid hyperemesis syndrome (CHS) present frequently to the emergency department. Previous case studies suggest dramatic symptomatic improvement with topical capsaicin treatment. This exploratory study examined the potential effectiveness of topical capsaicin in patients with nausea and vomiting due to a suspected CHS exacerbation. Methods: This was a double-blind, randomized placebo-controlled pilot trial. Adults who presented with vomiting suspected to be from CHS were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…A recent prospective study compared capsaicin with placebo in a double-blind randomized trial. 13 The authors found a reduction of nausea 60 minutes after capsaicin application. However, the authors questioned their findings in light of underpowering and potential selection bias.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent prospective study compared capsaicin with placebo in a double-blind randomized trial. 13 The authors found a reduction of nausea 60 minutes after capsaicin application. However, the authors questioned their findings in light of underpowering and potential selection bias.…”
Section: Discussionmentioning
confidence: 96%
“…Most patients were younger, long-term daily cannabis users and displayed typical CHS patterns of chronic cannabis consumption, abdominal pain, and relief with hot showers. 1-4,10,11,13,16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the legalization of cannabis continues to spread in North America, it has become increasingly important for physicians to recognize and treat cannabinoid-related syndromes. In this secondary analysis of a randomized controlled trial that studied the effect of topical capsaicin on patients presenting to the emergency department (ED) with cannabinoid hyperemesis syndrome (CHS), we describe symptomatology and return visits in patients suffering from CHS [1].…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto al tratamiento del SHC, sólo se han publicado 2 ensayos clínicos hasta la fecha, ambos en 2020, comparando haloperidol frente a ondansetrón (Ruberto et al, 2020) y capsaicina frente a placebo (Dean et al, 2020), con una treintena de pacientes en cada uno. Ambos fármacos han demostrado ser eficaces para el control de las náuseas, aunque son necesarios nuevos ensayos con un número mayor de pacientes y otros fármacos a priori útiles, como es el caso del droperidol (Lee, Greene y Wong, 2019) .…”
unclassified